Improve performance of soy protein adhesives with a low molar ratio melamine-urea-formaldehyde resin. (June 2020) - Jiang, Ke; Zhang, Jialin; Xia, Sanshan; Ou, Chuan; Fu, Chengang; Yi, Maoyu; Li, Wei; Jing, Mingwei; Lv, Wenxin; Xiao, Hui
Abstract: In this study, the low molar ratio melamine-urea-formaldehyde (MUF) resin and sodium hydroxide were used to modify soy protein adhesives, and the addition of MUF was studied as the influencing factor, the properties of soy protein adhesives, formaldehyde emission and bonding strength were studied. The results showed that the solid content and viscosity of the adhesives were suitable for the application of wood adhesives, the formaldehyde emission and wet shear strength of plywood prepared by soybean protein adhesive modified by MUF with 30% addition were 0.38mg/L and 1.25 MPa. Moreover, based on the analysis of the free formaldehyde content of the adhesive and the formaldehyde emission of plywood, it can be inferred that most of the free formaldehyde in the plywood was derived from the unreacted methyl group during the hot pressing process.